Empathy Matters: Exploring Teacher-Student Dynamics and Student Outcomes in Professional Undergraduate Courses - Gupta, Mansi; Mahajan, Diksha; Kour, Jaswinder (Journal of Engineering Education Transformations, 2026)
The present study investigates the pivotal role of teacher empathy in promoting positive, cognitive, and psychological outcomes among undergraduate students taking professional courses. Drawing upon insights from Interpersonal Theory, the research explores the intricate dynamics of teacher empathy on student outcomes mediated by teacher-student interactions within the professional educational context. Utilizing quantitative data gathered through surveys and employing machine learning techniques for analysis, the study synthesizes contemporary research with established educational literature highlighting empathy’s profound impact on learning. Emphasizing the dual responsibility of educational institutions in nurturing both intellectual and emotional development, the study underscores empathy’s intrinsic significance within the professional education system. The results reveal that the quality of teacher-student interaction significantly mediates the relationship between teacher empathy and student outcomes. Specifically, findings indicate that emotional support, effective classroom management, and instructional support serve as key mechanisms through which teacher empathy influences student cognitive and psychological well-being. This research contributes to a deeper understanding of the interplay between empathy, teacher-student dynamics, and student outcomes, thereby informing strategies for enhancing educational practices and student success.